De rerum humanarum emendatione consultatio catholica - education for co-existence = De rerum humanarum emendatione consultatio catholica - éducation à la coexistence = De rerum humanarum emendatione consultatio catholica - educazione alla coesistenza - Dancák, Pavol (Philosophy & canon law, 2018)
John Amos Comenius created a universal education system aiming for emendatio rerum humanarum, that is, improvement of all things human as he claimed that people live as prisoners in Plato’s cave, immersed in confusion and chaos. For Comenius, the boundless act of will is slavery. The true free will is prudent, that is, in line with God’s will. It must be in relation to what is universal and true. The true free will gives people a chance to assume their own place in the world as human beings that co-exist with others.